TOWARD SUSTAINABLE CITIES AND COMMUNITIES, THROUGH REVITALIZATION OF POTTERY URBAN KAMPONGS IN MALANG - Ramdlani, Subhan (MATTER: International Journal of Science and Technology, 2018)
One of the Sustainable Development Goals (SDG’S), Sustainable Cities and Communities, can be achieved by making cities and communities inclusive, safe, resilient and sustainable. The efforts undertaken is ensuring access to all decent communities, safe and affordable basic services, and slum area management. One of the methods is the revitalization process of urban kampongs. Malang City, has 17 urban kampongs with different potentials, both natural potency and its human resources. That is a form of settlement in the usual area with features such as: the population still carries the nature and behavior of life that is interwoven in close family ties and have distinctive regional characteristics. Decreased environmental quality, high density and limited economic access of citizens, became the basis for the selection of regional revitalization measures. Thematic means determining the direction of arrangement based on the potential of different kampong between kampongs. The methods begins with identification and understanding of economic-based as a vital factor for generators. The kampong of pottery vessel farmers is one of the kampongs with hereditary potential that began to decline its image. Its found spots with the potential space and craftsmanship expertise scattered in the kampong. Analysis of infrastructure potential that includes accessibility, green space, and economic potential analysis can validate the direction of revitalization. This revitalization is also city-based to enhance heritage tourism in the city center as the results. With this revitalization, pottery vessel settlements will be better prepared to welcome sustainable development, through achieving sustainable urban and residential environments.